Legal Implications of Internet Service Disruptions on Late Payment Penalties in Digital Consumer Transactions - Labibah, Hanin Alya; Damayanti, Miranda; Lestari, Arum Ayu; Setiawan, Galih Nicky Roby; Ningsih, Yuli Pertiwi (Journal of Development Research, 2026)
The development of digital technology has made internet services the primary means of conducting transactions; however, internet service disruptions often cause legal problems, especially related to late payments and the determination of the parties' responsibilities. This study aims to analyze the legal implications and forms of consumer protection for losses arising from internet service disruptions in digital transactions. The research method in this study is normative legal research with a legislative and conceptual approach. The results of the study show that late payments due to internet service disruptions can be categorized as force majeure as long as they meet elements beyond their control and cannot be predicted. In these conditions, consumers cannot be burdened with responsibility in the form of late fines or compensation due to the non-fulfillment of the elements of fault in default. In addition, the rigid application of the fine clause without considering the factual conditions is contrary to the principle of good faith and the principle of fairness in the agreement. In conclusion, internet service disruption in digital transactions has significant legal implications, especially in determining whether there is a default and the responsibility of the parties. If the disruption is proven to be force majeure, then the consumer cannot be burdened with the obligation of compensation or late fines due to the non-fulfillment of the elements of fault in default. It is necessary to strengthen force majeure through the restriction of standard clauses that are detrimental to consumers in digital transactions.